2008
DOI: 10.1016/j.dnarep.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Turning off the G2 DNA damage checkpoint

Abstract: In response to DNA damage, cells activate checkpoints to delay cell cycle progression and allow time for completion of DNA repair before commitment to S-phase or mitosis. During G2, many proteins collaborate to activate Chk1, an effector protein kinase that ensures the mitotic cyclindependent kinase remains in an inactive state. This checkpoint is ancient in origin and highly conserved from fission yeast to humans. Work from many groups has led to a detailed description of the spatiotemporal control of signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Because the stability of Rad17 is regulated by proteasome-dependent protein degradation during checkpoint recovery (1)(2)(3)21), the involvement of proteasomal protein degradation was examined. Exposure to the proteasome inhibitor MG132 did not affect the increase in Rad17 phosphorylation induced by SU6656 (Fig.…”
Section: Sfk Activity Is Required For G 2 Dna Damage Checkpointmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the stability of Rad17 is regulated by proteasome-dependent protein degradation during checkpoint recovery (1)(2)(3)21), the involvement of proteasomal protein degradation was examined. Exposure to the proteasome inhibitor MG132 did not affect the increase in Rad17 phosphorylation induced by SU6656 (Fig.…”
Section: Sfk Activity Is Required For G 2 Dna Damage Checkpointmentioning
confidence: 99%
“…Following checkpoint activation, several protein phosphatases and ubiquitin ligases target the activated checkpoint proteins including Rad17 (21), Claspin (22)(23)(24), and Chk1 (25)(26)(27)(28)(29)(30). The direct dephosphorylation and degradation of checkpoint proteins promote the termination of checkpoint signaling (1)(2)(3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery from the checkpoint arrest requires Chk1 dephosphorylation, which in S. pombe is catalyzed by the type 1 phosphatase Dis2 (den . This and additional phosphatases have been implicated in the inactivation of human Chk1, as have additional mechanisms including ubiquitin-dependent proteolysis (Calonge and O'Connell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recovery from the checkpoint arrest requires Chk1 dephosphorylation, which in S. pombe is catalyzed by the type 1 phosphatase Dis2 (den . This and additional phosphatases have been implicated in the inactivation of human Chk1, as have additional mechanisms including ubiquitin-dependent proteolysis (Calonge and O'Connell, 2008).Molecular details of how the phosphorylation of the C-terminal domain activates the N-terminal kinase domain are poorly understood, though are clearly important to delineate. Structural studies of human Chk1 showed the kinase domain to be in an open conformation (Chen et al, 2000); that is, this domain does not require activating phosphorylation that is commonplace in many protein kinases.…”
mentioning
confidence: 99%